Does Immigration Affect the Phillips Curve? Some Evidence for Spain - Samuel Bentolila; Juan José Dolado; Juan F. Jimeno (Kiel Institute for the World Economy (IfW), 2007)
This paper examines the evolution of the Phillips Curve (PC) for the Spanish economy since 1980. In particular, we focus on what has happened since the late 1990s. Since 1999 the unemployment rate has fallen by almost 7 percentage points, while inflation has remained relatively subdued around a plateau of 2%- 4%. Thus, the slope of the PC has become much flatter. We argue that this favorable evolution is largely due to the huge rise in the immigration rate, from 1% of the population in 1994 to 9.3% in 2006. We derive a New Keynesian Phillips curve accounting for the effects of immigration, a variable which is found to shift the curve if preferences and bargaining power of immigrants and natives dier. We then estimate this curve for Spain since 1980 and find that while the fall in unemployment over the last 8 years comes along with an increase in inflation of 2.2 percentage points per year, the increase of the relative unemployment rate of immigrants vis-?-vis natives accounts for an ofsetting 0.9 percentage points drop in the inflation rate per year.
Keywords: J64; E31; 330; Phillips curve; immigration; Phillips-Kurve; Einwanderung; Schätzung; Spanien